Eksistensi Budaya Pijat Bayi - Ida Bagus Wiryanatha (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Massage is one of the health-related traditions practiced. Massage culture is now not only practiced in an empirical setting, but has also become part of the behavior of paramedical actions. This effort is made to balance the treatment of giving drugs to toddlers, which frequently result in unintended side effects. Baby massage is one of the non-pharmacological therapies for infant sleep deprivation. Touching the baby can cause the release of endorphin hormones, which reduce pain and reduce the frequency of crying, and thus massage improves the baby's sleep quality. The research employs structural functionalism theory in conjunction with an ayurvedic approach. Data collection methods include observation, interviews, literature review, and documentation. Purposive sampling was used in the sampling technique. The study included 18 children aged one to five, ranging in age from one to five years. According to the findings, baby massage using specific techniques can improve sleep quality.